Identification of Relevant Genes with a Multi-Agent System using Gene Expression Data - Márquez, Edna; Savage, Jesús; Lemaitre, Christian; Berumen, Jaime; Espinosa, Ana; Leder, Ron (IntechOpen, 2011)
None